Fast Copy - Jenkins, Dan (Book collections on Project MUSE., 2001)
In 1935 Betsy Throckmorton's father lures her from a New York job with Time magazine back to Claybelle, Texas, with the promise that she can be the editor of his Claybelle Standard-Times. Betsy brings along her husband, Ted Winton, an easterner and Yale graduate to whom she is constantly explaining Texas. Ted will run Ben Throckmorton's radio station, KVAT, where Booty and Them Others sing in rivalry with the better known WBAP Light Crust Doughboys. In Texas, it's the middle of the Depression and the Drought. And Prohibition is barely over, liquor still a controversy. Every city has its hobo c.